Pilot study of a longitudinal integrated disaster and military medicine education program for undergraduate medical students. Issue 20 (15th May 2020) - Tsai, Yi-Da; Tsai, Shih-Hung; Chen, Sy-Jou; Chen, Yin-Chung; Wang, Jen-Chun; Hsu, Chia-Ching; Chen, Ying-Hsin; Yang, Tse-Chun; Li, Chih-Wei; Cheng, Cheng-Yi
Abstract : Abstract: Disaster medicine education in medical curricula is scarce and frequently nonexistent. It is reasonable to initiate educational approaches for physicians in this field at the medical school level. An understanding of disaster medicine and the health care system during massive casualty incidents has been recommended as an integral part of the medical curriculum in the United States and Germany. The goal of the reformed curriculum was to develop a longitudinal integrated disaster and military medicine education program extending from the first year to the sixth year based on previously separated clinical and military medicine topics. Emergency medicine physicians, military emergency medical technicians, and Tactical Combat Casualty Care instructors formed an interprofessional faculty group and designed a learning curriculum. A total of 230 medical students participated in the revised disaster preparedness curriculum. Satisfaction survey response rates were high (201/230, 87.4%). Most of the free-text comments on the program were highly appreciative. The students considered the number of teaching hours for the whole program to be adequate. The students showed significant improvements in knowledge and judgment regarding disaster medicine after the program. We found that medical students were highly interested, were appreciative of, and actively participated in this longitudinal integrated disaster and military medicine education program, but gaps existed between the students' scores and the educators' expectations. The educators believed that the students needed more disaster preparedness knowledge and skills. Abstract : Supplemental Digital Content is available in the text